Assessment of hand superficial oxygenation during ischemia/reperfusion in healthy subjects versus systemic sclerosis patients by 2D near infrared spectroscopic imaging. (March 2018) - Jalil, Bushra; Hartwig, Valentina; Salvetti, Ovidio; Potì, Luca; Gargani, Luna; Barskova, Tatiana; Matucci Cerinic, Marco; L'Abbate, A.
Highlights: NIR Imaging of the whole hand is applied to five normal volunteers and five SSc patients. Results show significant differences in microcirculation in hand skin of healthy volunteers and SSc patients. The image processing presented here allows to get a comprehensive view of the state of the microcirculation. Abstract: Background and objective: Patients affected by systemic sclerosis (SSc) develop functional and structural microcirculatory dysfunction, which progressively evolves towards systemic tissue fibrosis (sclerosis). Disease initially affects distal extremities, which become preferential sites of diagnostic scrutiny. This pilot investigation tested the hypothesis that peripheral microcirculatory dysfunction in SSc could be non-invasively assessed by 2D Near Infrared Spectroscopic (NIRS) imaging of the hand associated with Vascular Occlusion Testing (VOT). NIRS allows measurement of hemoglobin oxygen saturation (StO2 ) in the blood perfusing the volume tissue under scrutiny. Methods: In five normal volunteers and five SSc patients we applied a multispectral oximetry imaging device (Kent camera, Kent Imaging, Calgary, Canada) to acquire StO2 2D maps of the whole hand palm during baseline, ischemia and reperfusion phase. Results: We found significant differences between controls and SSc patients in basal StO2 (82.80 ± 2.51 vs 65.44 ± 7.96%, p = 0.0016), minimum StO2 (59.35 ± 4.29 vs 40.73 ± 6.47%, p = 0.0007), final StO2 (83.83 ± 4.09 vs 68.84 ± 11.41%, p = 0.02) and time to maximum StO2 (40 ± 12.25 vs 62 ± 4.47 s, p = 0.005). Conclusions: This is, to our knowledge, the first application of 2D NIRS imaging of the whole hand to the investigation of microvascular dysfunction in systemic sclerosis. The image processing presented here considered the StO2 in the entire hand allowing a comprehensive view of the spatial heterogeneity of microvascular dysfunction.